University of Washington library, Seattle, ca. 1905 - Webster & Stevens
This library is probably located in the basement of Denny Hall. It soon moved to the Washington State Building, which was built in 1909 for the Alaska-Yukon-Pacific Exposition. This building served as the library until the completion of the Suzzallo Library in 1926. Handwritten on sleeve: U of W Library. 1 glass negative: b&w; 8 x 10 in.; sulfiding